THE PREPARATION OF OWNER ESTIMATE IN RIG SERVICE CONTRACTS IN UPSTREAM OIL AND GAS BUSINESS ACTIVITIES ACCORDING TO LEGAL CERTAINTY PRINCIPLES. - Radjagoekgoek, Robert Pangihutan (Universitas Pelita Harapan, 2023)
As one of the vital and strategic natural resources, due to its vital role that could impact society, oil and gas is one of the sources of state revenue to support national development. To implement Article 33 of the 1945 Constitution, in particular to realize the welfare and prosperity of the people, UU Migas No 22, 2001 mandated SKK Migas to oversee upstream activity done by contractors (KKKS).Contractors conduct rig procurement processes with their Owner Estimate (OE) in alignment to Perpres No 12, 2021 and PTK 007, 2017. Due to that reason, legal certainty is needed to deal with problems at the implementation level.This dissertation research covers two legal issues, namely the regulation and implementation of the preparation of the HPS Value in the Rig contract.The theoretical basis used is agreement theory, legal certainty theory and Per Se Illegal and Rule of Reason approach. The research analysis is using normative juridicals which are supported by empirical studies.The result of this research concludes that normatively, OE preparation guidelines provide multiple interpretations, inconsistencies and a legal vacuum.In practice, problems related to aspects of legal certainty, namely HPS offers are not confidential and/or confidential, extreme price cut due to offers below 80% of HPS are being allowed, the existence of negotiations even though the price offer is already the lowest and below the HPS . It opens for conspiracy in the procurement. For this reason, it is necessary to amend Perpres and PTK 007 in order to achieve compliance according to the principles of agreement, legal certainty and fair business.The change in regulation will provide legal certainty, efficiency and effectiveness so that SKK Migas and KKKS and Rig Providers can carry out upstream business activities properly and optimally to support the social welfare of the Indonesian. Keywords: Oil and Gas, Owner Estimates Development, KKKS & Rig Provider